Abrupt shear thickening of aqueous solutions of hydrophobically modified poly(N,N `-dimethylacrylamide-co-acrylic acid) - Lele, Ashish K.; Shedge, Aarti; Badiger, Manohar V.; Wadgaonkar, Prakash; Chassenieux, Christophe (Macromolecules, 2010)
We report some new and interesting observations on the abrupt and large shear-induced thickening of aqueous solutions of hydrophobically modified poly(N,N'-dimethylacrylamide-co-acrylic acid). High molecular weight copolymer was prepared by free radical copolymerization of N,N'-dimethylacrylamide [DMA] and acrylic acid [AA] and was subsequently modified to different extents using a hydrophobic compound, namely, 3-pentadecylcyclohexylamine [3-PDCA], which is derived from a renewable resource material, cashew nutshell liquid [CNSL]. The structural elucidation of the base copolymer and the hydrophobically modified copolymers was performed by (1)H and (13)C NMR spectroscopy. The zero shear viscosities [eta(0)] of the hydrophobically modified polymers were lower than that of the precursor poly(N,N'-dimethylacrylamide-co-acrylic acid) until some critical polymer concentration, which increased with increase in hydrophobic modification. Above the critical concentrations, the eta(0) of the hydrophobically modified copolymers surpassed that of the precursor at the same concentration. At moderate shear rates some of these hydrophobically modified copolymers exhibited an abrupt shear-induced thickening in which the viscosity of the samples increased severalfold. We show here from creep experiments that thickening occurs only when the shear rate reaches a critical value, (gamma) over dot(crit), and that the thickened samples can be trapped in different metastable states by controlling the applied stress. Interestingly, the shear thickened samples showed further thickening upon decreasing the applied stress. Eventually, the metastable samples revert to their equilibrium states at characteristic time that depends on (small) probe stress.

Ascertaining universal features of yielding of soft materials - Kamble, Samruddhi; Pandey, Anurag; Rastogi, Sanjay; Lele, Ashish K. (Rheologica Acta, 2013)
Many metastable complex fluids, when subjected to oscillatory shear flow of increasing strain amplitude at constant frequency, are known to show a characteristic nonlinear rheological response which consists of a monotonic decrease in the elastic modulus and a nonmonotonic change in the loss modulus. In particular, the loss modulus increases from its low strain value, crosses the elastic modulus, and then decreases with further increase in the strain amplitude. Miyazaki et al. (Europhys Lett 75:915-921, 2006) proposed a qualitative argument to explain the origin of the nonmonotonic nature of the loss modulus and suggested that in fact this response could be universal to all complex fluids if they are probed in a certain frequency window in which the fluid is dominantly elastic in the small strain limit. In this letter, we confirm their hypothesis by showing that a wide variety of complex fluids, irrespective of their thermodynamic state under quiescent conditions, indeed show the aforementioned characteristic nonlinear response. We also show that the maximum relative dissipation during yielding occurs when the imposed frequency resonates with the characteristic beta relaxation frequency of the fluid.
Keywords: Colloidal suspensions; Entangled melts; Gels; Glasses; Microgels; Rheology; Yielding

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2018)
Two key assumptions are usually made while deriving analytical solutions of coupled kinetics and transport equations in a single channel on the cathode plate of a proton exchange membrane fuel cell (PEMFC). These are: plug flow and uniform oxygen concentration along the depth of the channel. However these assumptions are not always valid under typical operating conditions of a PEMFC, and particularly so at high current density. In this article we relax these two assumptions and present approximate analytical solutions of the governing equations using the methodology of separation of variables followed by power series solution. Spatial profiles of oxygen concentration and current density were derived, which led to the final derivation of a comprehensive current-potential relationship (polarization curve) in the reaction-controlled regime of an operational PEMFC. We compare polarization curves predicted by the present model with predictions of the earlier analytical model and also with a complete 3D-simulation of the same flow geometry and operation conditions. The local profiles of oxygen concentration and the polarization curve predicted by the present model compare far better with the 3D simulations than the earlier analytical model. While this comparison highlights the importance of the effects of finite oxygen diffusion rate and velocity profile in the channel on the polarization curves, it also points to other important factors that affect the current-potential relation.

Analytical solutions of an isothermal two-dimensional model of a cathode flow channel in transport limited operational regimes of a proton exchange membrane fuel cell - Thosar, Aniket U.; Lele, Ashish K. (Chemical Engineering Science, 2019)
In the quest for obtaining accurate closed-form analytical expressions for polarization curve of a proton exchange membrane fuel cell (PEMFC), we have recently presented a two-dimensional model that accounts for oxygen concentration gradient and velocity gradient along the depth of a cathode flow channel. The model was developed for the case when Tafel kinetics of oxygen reduction reaction (ORR) on the cathode governs the overall rate of oxygen consumption. An improved match between predictions of the model and full three-dimensional simulations was obtained over the entire range of current density compared with earlier models which assumed homogenous oxygen concentration in the channel depth and plug flow velocity profile. In reality however, ORR kinetics is often not the rate limiting step for oxygen consumption in the cathode catalyst layer (CCL) at high current density since the Tafel kinetics is modulated by transport resistances in the CCL. In this article, we extend our two-dimensional analytical model to two different transport-limited regimes of CCL operation namely, slow oxygen transport across the CCL and slow proton transport across the CCL. We compare model predictions with results of full three-dimensional simulations in both cases and show that they are in excellent agreement even in these transport limited operational regimes of PEMFC. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Analytical modelling; Polarization curve; Proton exchange membrane fuel cells; Transport resistance

ABPBI-based hollow fiber membranes for forward osmosis (FO) possessing low reverse salt flux - Thorat, Nitin M.; Lele, Ashish K.; Kharul, Ulhas K. (Desalination and Water Treatment, 2024)
The poly(2,5-Benzimidazole), known for its excellent thermochemical stability, was evaluated as a membrane material for forward osmosis. The dope in methane sulfonic acid was used to make hollow fiber membranes. The availability of bound MSA in HFMs was compared with its neutral form. Aqueous solutions of two common salts reported for FO (NaCl and MgCl2) were used as a draw solution at varying concentrations. The performance was determined in terms of water flux and reverse salt flux. The long-term performance of the membrane was assessed. The heat pretreatment of membranes was beneficial in offering low reverse salt flux, a crucial parameter in FO. The heat treatment at 350 degrees C exhibited excellent performance of low-RSF, irrespective of the draw solute used. The presence of MSA in the membrane matrix was found to be beneficial. Present HFMs exhibited reverse salt flux as low as 0.003 mol m-2 h-1 using 2 mol L-1 MgCl2 as a draw solution. The water flux of present membranes was lower than that of reported FO-membranes, which is attributable to the larger thickness of the present membranes. The findings will be used to make ABPBI-based membranes in thin form to elevate the fluxes and their practical applicability.
Keywords: ABPBI; Forward osmosis; Hollow fiber membrane; Low reverse salt flux